P14.11 Severe treatment-induced myelosuppression is more frequent in female malignant glioma patients and associated with reduced overall survival. (9th September 2021) - Zeiner, P S; Filipski, K; Forster, M; Voss, M; Fokas, E; Herrlinger, U; Harter, P N; Steinbach, J P; Ronellenfitsch, M W
Abstract: BACKGROUND: An association of treatment-related myelotoxicity with female gender has been previously suggested. However, a systematic analysis of the prognostic relevance of radiochemotherapy-related cytopenia involving the different blood cell lineages is lacking. MATERIAL AND METHODS: We retrospectively analyzed cytopenia during temozolomide-based concomitant radiochemotherapy (RCT) in 493 glioma patients. Histological grading, molecular pathology, surgical procedures and median overall survival (OS) were recorded. The extent of cytopenia was correlated with gender and outcome. RESULTS: Treatment-induced severe cytopenia (leuko-, lympho-, neutro- and thrombocytopenia) occurred much more often in female than in male glioma patients (40.8 vs. 13.9%, p-value <0.0001). In female patients with IDH-wildtype high-grade astrocytomas there was a negative correlation of severe leuko-, lympho- and thrombocytopenia during temozolomide RCT with OS (36 vs. 54, 37 vs. 54 and 36 vs. 57 weeks, respectively; all p-values <0.05). In male patients there was also a trend for this unfavorable effect. Additionally, severe cytopenia correlated with reduced temozolomide dose exposure during RCT (all p-values <0.05 in total cohort) and reduced dose exposure was independently associated with worse OS (p-values <0.05 in the total and female cohort). CONCLUSION: Our data confirm that women are at higher risk for treatment-induced cytopenia during RCT which is associated with a significant decrease in OS. From our data, it appears plausible that reduced temozolomide dose exposure during RCT is at least in part responsible for this finding. Immunosuppression of patients with severe cytopenia may be an independent contributor to adverse outcome.